1994
DOI: 10.1152/ajplung.1994.266.1.l2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-induced lung neutrophil accumulation and oxygen metabolite-mediated lung leak in rats

Abstract: We found that intratracheal administration of recombinant interleukin-1 alpha (IL-1) into rats rapidly (< 5 h) increased neutrophils in lung lavages and caused an acute edematous lung injury which was reflected by lung albumin accumulation (lung leak) and histological abnormalities (perivascular cuffing). These IL-1-dependent processes were inhibited by prior administration of recombinant IL-1 receptor antagonist and did not occur following administration of heated IL-1. Several lines of evidence suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…PQ-induced ROS can activate intracellular transcription factors such as NF-κB [13], thereby enhancing IL-1β expression. IL-1β can upregulate the expression of endothelial intercellular adhesion molecules essential for the recruit of inflammatory cells to an area of inflammation [18]. In an in vivo experiment, we found that the production of IL-1β and IL-18 in the PQpoisoning group of rats, BALF increased obviously in a time-dependent manner compared with the control.…”
Section: Discussionmentioning
confidence: 73%
“…PQ-induced ROS can activate intracellular transcription factors such as NF-κB [13], thereby enhancing IL-1β expression. IL-1β can upregulate the expression of endothelial intercellular adhesion molecules essential for the recruit of inflammatory cells to an area of inflammation [18]. In an in vivo experiment, we found that the production of IL-1β and IL-18 in the PQpoisoning group of rats, BALF increased obviously in a time-dependent manner compared with the control.…”
Section: Discussionmentioning
confidence: 73%
“…Discussion IL-Ia has been shown to increase neutrophil adhesion to endothelium (37,38) and lung neutrophil accumulation (39), to induce its own gene expression in endothelial cells (40), to stimulate the production of lipid mediators (13,17,19,20,41) and the synthesis of collagen by fibroblasts (42), and to induce basic fibroblast growth factor production by vascular smooth muscle cells (43). This information, in the aggregate, provides a powerful rationale for the postulate that some of the activities of IL-I may playa role in the development of chronic inflammatory pulmonary hypertension.…”
Section: Lung Histologymentioning
confidence: 97%
“…Additionally, glibenclamide's inhibitory effect on neutrophil migration is somewhat indirectly mediated by its inhibition of NLRP3 inflammasome assembly. NLRP3 inflammasome is the key for IL-1 β maturation, and IL-1 β upregulates the expression of endothelial intercellular adhesion molecules essential for the recruitment of neutrophils to the area of inflammation [9496]. …”
Section: Mechanisms Of Glibenclamide Underlying Its Anti-inflammatmentioning
confidence: 99%